1987
DOI: 10.1080/08940630.1987.10466207
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Exposures of Washington Commuters

Abstract: The potential for directly monitoring public exposure to air pollutants has been realized with the development of personal exposure monitors. The microenvironmental approach to exposure assessment involves monitoring the concentrations within microenvironments thought to contribute significantly to a population's total exposure. This paper focuses on the commuting microenvironment, because of the suspected large contribution that commuting makes to the total population exposure to carbon monoxide (CO). In part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
1

Year Published

1988
1988
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 12 publications
2
24
1
1
Order By: Relevance
“…The highest CO concentrations are typically observed in dense traffic, when a group of vehicles is accelerating in traffic lights (Colwill and Hickman, 1980). Contrary to Flachsbart et al (1987), Clifford et al (1997) did not find a significant association of the CO levels with vehicle speed. They report considerable day-to-day variation of CO concentration.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…The highest CO concentrations are typically observed in dense traffic, when a group of vehicles is accelerating in traffic lights (Colwill and Hickman, 1980). Contrary to Flachsbart et al (1987), Clifford et al (1997) did not find a significant association of the CO levels with vehicle speed. They report considerable day-to-day variation of CO concentration.…”
Section: Introductionmentioning
confidence: 57%
“…The concentrations of CO and VOCs were higher in the personal samples of car drivers than in personal samples of cyclists (Van Wijnen et al, 1995). Flachsbart et al (1987) observed a relationship between CO level and automobile speed. The average CO level is shown to decrease with increasing speed.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Similar to an approach developed by Flachsbart et al, 13 the variance of solid waste estimated to be due to each socioeconomic factor was expressed as a percentage of the mean household level of solid waste generated per day. The equation had the following form:…”
Section: Variance Component Analysismentioning
confidence: 99%